Developing evaluation of signage for people with dementia. Issue 3 (5th September 2019) - Gresham, Meredith; Taylor, Liz; Keyes, Sarah; Wilkinson, Heather; McIntosh, Danielle; Cunningham, Colm
Abstract : Purpose: The purpose of this paper is to to describe development of a framework for use in the evaluation of the effectiveness of signage to assist people with dementia. Design/methodology/approach: The study consisted of two parts. Workshops held in both Sydney and Edinburgh using "world café" methodology with 28 knowledgeable participants produced a pool of statements. These were subsequently used in a three-round Delphi process administered to 38 participants in order to generate ideas and develop consensus content for a signage evaluation framework. Findings: This process resulted in a framework consisting of Delphi statements which had a 70 per cent level of agreement and a series of prompt questions. Both intrinsic factors and wider environmental, extrinsic factors in signage for wayfinding were identified. Research limitations/implications: Limitations of this study were the small number of participants, including only four people with dementia, and the unresolved problems inherent in designing signage that may simultaneously be universally relevant and readily understood, yet meets the idiosyncratic needs of each individual living with dementia. Originality/value: As there is little prior work in this field concerning signage use by people with dementia, this framework provides an original preliminary tool that may be used in further research on evaluating signage effectiveness. In designing signage and testing its effectiveness, it was concluded that the direct involvement of people with dementia is essential.